2016
DOI: 10.1111/nmo.12828
|View full text |Cite
|
Sign up to set email alerts
|

Early life adversity in piglets induces long‐term upregulation of the enteric cholinergic nervous system and heightened, sex‐specific secretomotor neuron responses

Abstract: Background Early life adversity (ELA) is a risk factor for the later-life onset of gastrointestinal (GI) diseases such as irritable bowel syndrome (IBS); however, the mechanisms are poorly understood. Here, we utilized a porcine model of ELA, early weaning stress (EWS), to investigate the influence of ELA on the development and function of the enteric nervous system (ENS). Methods Female and castrated male (Male-C) piglets were weaned from their sow either at 15 d of age (EWS) or 28 d of age (late weaning co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 80 publications
1
55
1
1
Order By: Relevance
“…In line with the present findings, we have previously demonstrated that EWS pigs exhibited increased diarrheal disease in response to a live oral challenge with enterotoxigenic E. coli . (36) In addition, more recently we showed that EWS pigs exhibited a persistent, heightened sensitivity to neural-evoked secretomotor responses mediated largely by an upregulated cholinergic nervous system (28) that was more severe in EWS female pigs compared with Male-C pigs. Additional contributing factors contributing to diarrhea in EWS pigs could be the heightened excitability of intestinal mast cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with the present findings, we have previously demonstrated that EWS pigs exhibited increased diarrheal disease in response to a live oral challenge with enterotoxigenic E. coli . (36) In addition, more recently we showed that EWS pigs exhibited a persistent, heightened sensitivity to neural-evoked secretomotor responses mediated largely by an upregulated cholinergic nervous system (28) that was more severe in EWS female pigs compared with Male-C pigs. Additional contributing factors contributing to diarrhea in EWS pigs could be the heightened excitability of intestinal mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…(48) Another potential factor contributing to persistent ileal permeability in EWS females could be the increased cholinergic tone and acetylcholine release which was demonstrated in our previous study. (49) Given the female-specific response, potential estrogen effects are also a consideration as estrogen has been shown to both positively and negatively modulate intestinal barrier properties. (5052) However, given there were no differences in intestinal permeability between LWC Male-C and LWC female pigs at the 7 (prepubertal) or 20 week (pubertal) time point, the role of postnatal estrogens, while possible, does not fit with our the present findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether comparable changes occur in peripheral tissues namely in the gastrointestinal tract (GIT) that is endowed with the enteric nervous system (ENS) exhibiting a strikingly similar repertoire of neurons, nerve fibers, glia, neurotransmitters and modulators to that in the brain, is not known. In this issue of Neurogastroenterology & Motility, Medland et al (7) using an ELA model of early weaning stress (EWS) in pigs, where newborns are weaned on day 15 instead of day 28 (normal weaning)(8), demonstrate, for the first time in a large mammalian species, a sustained modulation of ileal enteric neuron number, phenotype, neuronal enzyme activity and mucosal epithelial cell neurosecretory functions. They also highlight a key contribution of sex to those alterations.…”
Section: Introductionmentioning
confidence: 99%